What Can Be Done to Reduce the Occurrence of Piracy in the Short and Long Run? - Olaf J. de Groot; Marc Vothknecht (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The problem of piracy and other forms of maritime security is actually less severe than many people perceive. Nevertheless, it is a problem that needs to be addressed. To solve the problems around Somalia, the naval involvement should continue, and effective punishment for piracy must be increased. Finally, in order to fight the long-term occurrence of piracy, a land-based solution must be found. Such a solution can only work when the focus is on building institutions and particularly the fight against corruption. There are other regions in the world that may succumb to piracy and where such land-based reforms can prevent piracy from being established in the first place.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330